Tippy- tippy - tippy, splash! - Fleming, Candace (Atheneum Books for Young Readers, 2014)
Fed up with the constant presence of rabbits in his house and yard, Mr. McGreely goes to the beach for some fun but the pesky pufftails will not give him a break.